Quality of knowledge in group decision support systems - Lima, Luís (2009)
In this work it is addressed the problem of knowledge evaluation in a VirtualECare Group Decision Supporting System (GDSS), in terms of an Multi-valued Extended Logic Programming language, which is aimed at sustaining online healthcare services. Indeed, reasoning with incomplete and uncertain knowledge have to be dealt with, due to the particular nature of the healthcare services, where the awful consequences of bad decisions, or lack of timely ones, demand for a responsible answer.